Debriefing as a Supportive Component for Registered Nurses in Transition. Issue 4 (July 2016) - Shinners, Jean; Africa, Larissa; Hawkes, Beth
Abstract : Debriefing is considered a positive approach used to evaluate learning, support communication, and explore emotions following simulation or a clinical experience. This article discusses the use of debriefing as an evolving strategy for new graduate nurses and focuses on the importance of structured clinical debriefing as a component to relieve stress while providing periods of reflection and cohesion.